2019
DOI: 10.1007/s00382-019-05014-6
|View full text |Cite
|
Sign up to set email alerts
|

Observationally constrained projection of the reduced intensification of extreme climate events in Central Asia from 0.5 °C less global warming

Abstract: Arid Central Asia is highly vulnerable to extreme climate events. Information on potential future changes in extreme climate events in Central Asia is limited. In this study, the performances of models from the Coupled Model Intercomparison Project phase 5 (CMIP5) in simulating climatological extremes in Central Asia are first evaluated, and a bias correction method is employed to constrain future projections. The responses of extreme climate events over Central Asia to future warming and, in particular, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 80 publications
3
34
0
Order By: Relevance
“…The human influence can be detected in the observed changes in both temperature (Peng et al 2019) and precipitation (Peng et al 2018). In addition, a stronger than global mean warming trend is projected for Central Asia in the twenty-first century and the changes are statistically significant (Christensen et al 2013, Mannig et al 2018, Peng et al 2020. The projected precipitation changes are less clear and not fully consistent (Christensen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The human influence can be detected in the observed changes in both temperature (Peng et al 2019) and precipitation (Peng et al 2018). In addition, a stronger than global mean warming trend is projected for Central Asia in the twenty-first century and the changes are statistically significant (Christensen et al 2013, Mannig et al 2018, Peng et al 2020. The projected precipitation changes are less clear and not fully consistent (Christensen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sillmann et al (2013a) evaluated the performance of the CMIP5 ensemble in simulating climate extremes indices as compared to reanalyses and the CMIP3 ensemble, as well as to observational indices at a global scale; they reported that the CMIP5 ensemble showed some improvements relative to CMIP3. Several continental and subcontinental assessments of twentieth century changes in extreme climate also have been undertaken; examples include Asia (Dong et al, 2017; Peng et al, 2020), North America (Yu et al, 2019), South America (Wu & Polvani, 2017), Africa (Diedhiou et al, 2018), Australia (Alexander & Arblaster, 2017), the United States (Thibeault & Seth, 2014), China (Jiang et al, 2015; Li et al, 2013), and the Tibetan Plateau region (Yin et al, 2019; You et al, 2018). Results of these studies show that the CMIP5 models are generally able to simulate climate extremes, but there are larger uncertainties in the tropics and subtropics (Bador et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although some models have more than one realization available, we only use the rst ensemble member to keep all GCMs being equally weighted in multimodel analysis. Previous studies also use the rst ensemble member in climate extreme assessment (e.g., Sillmann et al 2013;Ting et al 2015;Peng et al 2019). Meanwhile, only one ensemble member of GCMs participating in the CMIP5 are used as boundary conditions of the regional models in NA-CORDEX.…”
Section: Cmip5 Datamentioning
confidence: 99%
“…To assess its signi cance, the detected change is considered as "robust" when at least 75% of the models agree on the sign of the change. Similar strategies have been adopted in previous studies to assess the robustness of future climate change (Maloney et al 2014;Peng et al 2019;Chen 2020). Additionally, the study area is divided into nine regions, according to the de ned climatically consistent regions of the contiguous US (Karl and Koss, 1984), for regional-scale analysis of the projected climate extremes (Fig.…”
Section: Detection Of 15°c and 2°c Global Warmingmentioning
confidence: 99%
See 1 more Smart Citation